ANALISIS DIMENSI KNOWLEDGE WORKER DALAM MENINGKATKAN KNOWLEDGE MANAGEMENT PEGAWAI PADA SEKRETARIAT DAERAH KABUPATEN KERINCI - Ferry Siswadhi; Mauledy Ahmad (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
Knowledge management is an approach that relies on understandingorganizational tasks, namely understanding well how and when knowledgecreation must be supported, how to use the accumulated knowledge that has beencreated so that it can be made more productive. This study aims to describe thedimensions of knowledge work and knowledge management as well as explainthe influence of knowledge workers on knowledge management and explain theeffect of the dimensions of knowledge workers on knowledge managementthrough knowledge workers in employees at the Regional Secretariat of KerinciRegency. The dimensions of entrepreneurship used in this research areSymbolic-Analytic, Social Skill and Cilent Relationship and Instrinsic Nature.The population and sample in this study were all employees at the RegionalSecretariat of Kerinci Regency. The research design used is correlational so thatthe research method used is by using a questionnaire. Use AMOS as ananalytical tool with the Structural Equations Modelling (SEM) technique